2008
DOI: 10.1016/j.brainresrev.2007.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Combining modules for movement

Abstract: We review experiments supporting the hypothesis that the vertebrate motor system produces movements by combining a small number of units of motor output. Using a variety of approaches such as microstimulation of the spinal cord, NMDA iontophoresis, and an examination of natural behaviors in intact and deafferented animals we have provided evidence for a modular organization of the spinal cord. A module is a functional unit in the spinal cord that generates a specific motor output by imposing a specific pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
389
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 510 publications
(411 citation statements)
references
References 31 publications
21
389
0
1
Order By: Relevance
“…Strong evidence, notably through the concepts of central pattern generators and force fields (see resp. reviews by Grillner (2006) and Bizzi et al (2008)), supports the existence of such functional modules at the spinal level in vertebrate animals. For instance, Kargo and Giszter (2000) have demonstrated how a finite set of spinal motor primitives could account for the natural wiping reflex in the frog, showing that the central nervous system (CNS) could use such primitives to produce natural behaviors.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Strong evidence, notably through the concepts of central pattern generators and force fields (see resp. reviews by Grillner (2006) and Bizzi et al (2008)), supports the existence of such functional modules at the spinal level in vertebrate animals. For instance, Kargo and Giszter (2000) have demonstrated how a finite set of spinal motor primitives could account for the natural wiping reflex in the frog, showing that the central nervous system (CNS) could use such primitives to produce natural behaviors.…”
Section: Introductionmentioning
confidence: 65%
“…Indeed, they brought to light that movements were generated in a modular way by the spinal cord in frogs (for a comprehensive review, see Bizzi et al (2008)). More precisely, stimulating specific interneuronal areas of the spinal cord, they observed that the limb was moved in the direction of the same target posture (equilibrium point) whatever the initial position of the limb was.…”
Section: Motor Primitives and Forces Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) VF can effectively increase the inter-limb similarity of synergies and activation coefficients. (2) In the case of synergies, the improvement is achieved by reducing the interlimb muscle-weight differences of synergies (3). In the case of activation coefficients, the improvement is achieved by approximating the activation coefficient of the left arm towards the activation coefficient of the right arm.…”
Section: Resultsmentioning
confidence: 99%
“…Urra, A. Casals and R. Jané are with the Universitat Politècnica de Catalunya -BarcelonaTech and Institute for Bioengineering of Catalonia (IBEC), Baldiri Reixac 4, Tower I, 9 th floor, 08028, Barcelona, Spain (phone: +34 (93) 4039706; fax: +34 (93) 4039702; e-mail: ourra@ibecbarcelona.eu, acasals@ibecbarcelona.eu, rjane@ ibecbarcelona.eu) R. Jané is also with CIBER de Bioingeniería, Biomateriales y Nanomedicina, Spain. Our brain achieves motor coordination by combining simultaneous activations of diverse muscle groups known as synergies [2][3]. In this framework, a control structure is defined as the set of synergies and activation coefficients needed to perform a movement.…”
Section: Introductionmentioning
confidence: 99%